Analysis of Lightning Surge Characteristics on Transmission Tower - Md.Salah Uddin, Yusuf; Mohiuddin, Ahmad (2015)
Lightning performance of transmission lines is an important factor for the electric utility companies. Now a day, this matter is getting more priority with the increasing requirement for power quality. In order to understand the lighting surge phenomena clearly, the author used a reduced scale model of tower for the analysis. But in real life, the actual tower is subjected to the lightning. It is then necessary to analyze the characteristics of actual tower when subjected to lighting as in case of reduced scale model tower. So, the authors also simulate an actual tower to obtain the surge characteristics phenomena. In this case, the three-phase conductors and the earth wire have been considered for the analysis. The apparent characteristics of a tower may be influenced by the presence of an earth wire. However, this issue has been paid a little attention in the modeling of a tower for the well-known Numerical Electromagnetic Code (NEC-2) simulations. In this paper, firstly, a reduced scale model is analyzed in different aspect, and then the surge characteristics of an earth-wired tower as well as phase conductors of the tower struck by lightning are studied with the help of NEC-2 in case of direct and indirect stroke.